2018
DOI: 10.1038/s41598-018-23909-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evaluation of seed vigor by the absolute content of protein in seed within the same crop

Abstract: Seed vigor, an important index of seed quality, determines the potential for rapid and uniform emergence of plants. The objective of this study was to explore a rapid method for evaluating seed vigor. To analyze the correlation of seed traits and seedling traits related to seed vigor, we designed five experiments including nitrogen fertilizer, irrigation and seed sorting treatments in wheat. The results showed that only the absolute content of protein (ACP) in wheat seed was significantly correlated with plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 28 publications
1
40
0
Order By: Relevance
“…High seed vigor is aligned with potential of increasing growth and productivity agricultural productivity. Seed weight and seed nutrient content gives impact to plant growth at seedling period [46,47]. Earlier studies done to showed a close relationship between seed size or seed weight and early vigor in rice which reveals that rice seed with thin hull and large embryo are preferable for seed vigor [48].…”
Section: Effect Of Salinity On Seed Vigormentioning
confidence: 99%
“…High seed vigor is aligned with potential of increasing growth and productivity agricultural productivity. Seed weight and seed nutrient content gives impact to plant growth at seedling period [46,47]. Earlier studies done to showed a close relationship between seed size or seed weight and early vigor in rice which reveals that rice seed with thin hull and large embryo are preferable for seed vigor [48].…”
Section: Effect Of Salinity On Seed Vigormentioning
confidence: 99%
“…The aim of this study is to evaluate the incorporation of seed weight as a covariate into genomic predictions and association studies for three biomass traits in panel of elite maize inbred lines challenged by water withholding at the seedling stage. HKW is a commonly available information in most breeding programs and it is known to affect early plant growth and development [7].…”
Section: Discussionmentioning
confidence: 99%
“…DA-6 can increase protein contents in plants [1]. Moreover, genes, environmental conditions, and cultivation patterns also affect seed protein content, which is related to both wheat end use and seed vigour [1619]. However, the effects of spraying DA-6 after anthesis on wheat grain weight and seed protein content remain unknown.…”
Section: Introductionmentioning
confidence: 99%